A new compact printed ring bandpass filter structure for ISM band applications - Soufiane El Maimouni; Fouad Aytouna; Jamal Zbitou; Stephane Ginestar; Mohammed El Gibari (Bulletin of Electrical Engineering and Informatics, 2026)
We introduce a novel, compact bandpass filter (BPF) that employs Ring coupling through a microstrip design. This filter features a ring resonator that mainly relies on capacitive coupling to achieve its resonant characteristic. The results from experimental fabrication confirmed the expected performance of the filter, showing strong agreement between the simulated and measured S-parameters. The filter is built on a RO4003C substrate that is 1.52 mm thick, with a dielectric constant of 3.38 and a loss tangent of 0.0027. Designed for a center frequency of 5.72 GHz and a bandwidth of 930 MHz, it exhibits low insertion loss and effective signal rejection, as supported by advanced electromagnetic simulations. This flexible and efficient filter design represents a significant step forward, offering great potential for innovative communication systems and wireless power transmission, especially when integrated with 5.8 GHz straight-through antenna arrays for wireless energy harvesting.